PENDAMPINGAN DAN PENGUATAN KAPASITAS PENGURUS KELOMPOK LANSIA DI PERUM BUMI ASRI DADAPREJO MALANG (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The partner of this community service program is the administrator of the rw 9 elderly group Bumi Housing Asri Dadaprejo. Based on interviews with the Chairman's Mother RW 9, the Chairman of the Elderly Group, and the Treasurer of the Elderly Group, several obstacles were found, among others; Management exists but vacuum approximately 3 (three) years. This is due to the busyness of administrators in managing external activities in a social-community context. Thus, elderly activities in RW 9 are more likely to be absent; 2) The elderly group in RW 9 has actually been formed. Unfortunately, there is minimal participation. As for some who are active, they only follow the Elderly Posyandu and the Independent Elderly Program; 3) There is a longing and strong desire of the administrator to activate activities in his own environment so as to motivate togetherness and active participation in the RW 9 environment. This anxiety refers to the experience of 3 (three) years ago of elderly management where almost all were excited in participating in activities held in rw 9. Based on the analysis of the situation and problems faced by the elderly group management, the implementation team submitted a solution in the form of "Assistance and Strengthening the Capacity of the Elderly Group Management RW 9 Perum Bumi Asri Dadaprejo" through the agenda: 1) Assistance in mapping elderly social problems to restore the sense of concern and togetherness; 2) Assisting the preparation of routine activities of the elderly group to form an independent and professional management structure; 3) Development of administrators related to the implementation and evaluation of activity programs that make the elderly group feel "healthy, empowered and happy". The implementation of this group service program is carried out classically (sharing and upgrading individual capacity) in accordance with several topics; 1.) Basics of Organizational Governance at the regional level; 2.)Effective communication strategies and urban social interaction models; and 3.) Healthy, Empowered, and Happy Elderly Lifestyle. Thus, the external targets in this service program are; 1) Independence of administrators to map social problems and compile elderly community activities through the coordination of elderly group administrators on a regular basis, 2) Capacity to organize activities compiled by the administrators of the elderly group in mutually agreed activities, 3) Capacity to evaluate community activity administrators who are able to restore the togetherness and active participation of the elderly in rw 9, among others (1) Gymnastics of Healthy Elderly And (2) Profile books of elderly groups